Economic impact of individualized antimicrobial dose optimization in the critically ill patient in Spain - Grau, Santiago; Luque, Sonia; Ferrandez, Olivia; Benitez Cano, Adela; Rubio-Rodríguez, Darío; Rubio-Terrés, Carlos (Frontiers in Pharmacology, 2025)
ObjectiveTo estimate the economic impact of individualized dose optimization guided by antimicrobial therapeutic drug monitoring (TDM) in Spain, compared to no monitoring.MethodsA cost analysis of antibiotic treatment of critically ill patients, with and without TDM, was performed using a probabilistic Markov model (with second-order Monte Carlo simulations). Three scenarios were analyzed based on three published meta-analyses (Analysis 1: Pai Mangalore, 2022; Analysis 2: Sanz-Codina, 2023; Analysis 3: Takahashi, 2023).ResultsTDM, compared to the no-TDM option, generated according to the meta-analysis, a per patient expenditure of €195 (95%CI €194; €197) in analysis 1 or savings of -€301 (95%CI -€300; -€304) and -€685 (95%CI -€685; -€684) in analyses 2 and 3. The probability of TDM (vs. no-TDM) generating savings would be 39.4%, 63.5% and 79.7% in analyses 1, 2 and 3, respectively. This discrepancy in the results is due to methodological differences, in particular in the cure rate with TDM (vs. no-TDM) obtained in the meta-analyses: 12.2%, 16.6% and 16.0% more in analyses 1, 2 and 3, respectively.ConclusionIn critically ill patients undergoing antimicrobial therapy TDM, there is an increased likelihood of cure. However, the currently available data are not conclusive on the economic impact of such a therapeutic effect.